Effect of Imagining the Strategy of Play and Imagining the Motor Skill on Youths' Sport Performance in Karate - Ali Fathizadeh; Mehdi Sohrabi; Alireza Saberi Kakhki (University of Tehran, 2022)
Introduction: The present study aimed to determine the effect of imagining the play strategies in comparison with imagining the motor skills on performance during a sports competition course.Methods: Participants were 30 (19 men, 11 women) karatekas who were evaluated as upper than moderate in terms of performance level. In the beginning, participants' ability and past experiments in motor imagery were assessed. Then, they took part in a quasi-experimental design of one of three strategic imagery, movement imagery, or control groups. Each person immediately after combatting with an opponent performed the required action depending on the group and finally competed against the same previous opponent, again.Results: The results showed that karatekas had excellent imagery ability, especially in preserving the temporal characteristics of the movement, and at the past competitions, specifically before their matches, they had used both cognitive-general and cognitive-specific imagery. Also, the nonparametric analysis demonstrated that in the quasi-experimental design, the strategic imagery group gained a higher point difference during the post-test, however, the movement imagery or control group did not differ significantly.Conclusion: The research findings revealed that strategic imagery has more advantages compared to skill imagery, suggesting that strategies of play can be used between the matches as an effective factor in sports success.